Service Branding a Necessity for Service Providers - Chauhan, Vikrant; Kansal, Amit (Journal of Commerce and Trade, 2010)
A Brand is a promise - The American Marketing Association defines brand as “a name, term, sign, symbol or any other feature that identifies one seller’s product or service as distinct from that of other sellers”. But in general Branding is traditionally associated with products according to their distinct features. And it is believed the services are not required branding as services are intangible, inseparable, heterogeneous and perishable. We believe that these special features of service make it difficult for a prospective customer to evaluate a service before purchase, as is possible in the case of a product. Therefore, branding a service becomes even more important than branding a product, so that the brand communicates a promise and evokes trust in prospective customers. This article will aim at the issue of service branding.